Spam Filter Situs Jejaring Sosial Mahasiswa Menggunakan Regular Expression - Simon Salomon; Seng Hansun (ULTIMA InfoSys, 2017)
Spam is an unexpected and unsolicited email sent randomly indiscriminately, directly or indirectly by the sender who has no connection whatsoever with the recipient. The purpose of spam itself is to send information to the recipient, where the content of the sent message generally contains ads that offer nonessential products or illegal products, scams, promotional purposes, or spreading malware designed to hijack computers receiver. Based on the background of the problem, it is necessary anti-spam on a chat or dissemination of information in social networking using regular expression. From this study, the behavioral intention to use at level of 80% means that the user agrees that this website increases user interest in obtaining information and communication, and generates an immersion level of 80% which means the user is very focused when using the website. This website generates value by 98% precision and 98% recall that produce harmonic mean value of 97% so that it can be concluded that it has the precision and recall value harmonious. Index Terms—social networking, regular expression, spam, website